Enlargement of the Surface Area of High-Entropy Alloys with Acid Treatment as Positive Electrode for High Specific Capacitance Supercapacitors - Gülen, Mahir; Taş, Recep; Dünya, Hamza; Rajendrachari, Shashanka; Taş, Recep; Gülen, Mahir; Dünya, Hamza (Wiley-V C H Verlag Gmbh, 2025)
High-entropy alloys (HEAs), containing five or more elements in equal proportions, have recently made significant achievements in materials science due to their remarkable properties, including high toughness, excellent catalytic, thermal, and electrical conductivity, and resistance to wear and corrosion. This study focuses on a HEA composed of 23Fe-21Cr-18Ni-20Ti-18Mn, synthesized via ball milling. The alloy was treated with hydrochloric acid (HCl) to enhance its active surface area. The untreated HEA and the HCl-treated HEA (HEA-T) were then evaluated as potential cathode materials for supercapacitors (SCs). X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDX) confirmed that the HEA's composition and crystalline structure remained stable during acid treatment, with no new phases forming. The acid treatment significantly increased the surface area by ~20 times, the pore volume by ~10 times, and improved microstructural homogeneity. The HEA-T electrode demonstrated superior specific capacitance, lower internal resistance, and better cycling stability than the untreated HEA electrode. At 0.5 A/g current density, the specific capacitance (Csp) of the HEA-T was 600 F/g, approximately two times higher than the untreated HEA. This enhanced performance suggests that the HEA-T electrode could lead to the development of high-performance SCs.
Keywords: High Entropy Alloy (Hea); 23fe-21cr-18ni-20ti-18mn; Supercapacitors; Acid Treatment